Peritoneal Dialysis at Ibn Sina Hospital in Rabat: 10 years' experience - Meryem Benbella; Aziza Guennoun; Mohamed Belrhiti; Tarik Bouattar; Rabia Bayahia; Naima Ouzeddoun; Loubna Benamar (RDPLF, 2020)
Introduction:  The choice of dialysis modality has become an important decision that affects not only the country's health policy in the management of chronic end stage renal failure, but also the quality of life of patients and their survival. Peritoneal dialysis is an alternative for the treatment of these patients. The objective of our work is to report the epidemiological, clinical and biological results in the unit of PD, UHC of Rabat and to clarify the obstacles to the development of PD in Morocco.  Material and Methods:  We conducted a descriptive retrospective study in our PD unit from July 2006 to July 2017, including all patients who were in PD by choice or necessity and enrolled in the French Peritoneal Dialysis Registry (RDPLF).  Results: In 10 years, 159 patients were placed in PD, with an average age of 50.44 +/- 17.42 years and a sex ratio of 1.36. The indication for placement of setting in PD was by choice in 34% of the cases, social in 52% and medical in 14% of cases. Mechanical complications were dominated by catheter migrations. Infectious complications were represented by peritonitis, caused by poor of hygiene in 42% of cases. Conclusion: The obstacles to the development of PD are the lack of knowledge of the technique by the patients, as well as the prejudices or myths about the technique.